THE IMPACT OF BIOFLOCKS APPLICATION COMBINED WITH PROBIOTICS ON THE GROWTH PERFORMANCE OF WHITE LEG SHRIMP - Setyono, Bagus Dwi Hari; Azhar, Fariq; Paryono, Paryono (Buletin Veteriner Udayana; Vol. 11 No. 1 Pebruari 2019DO - 10.24843/bulvet.2019.v11.i01.p02, 2019)
Intensive shrimp farming was found many disease problems such as bacteria, viruses, or the presence of co-infection. One of the diseases was caused by viruses and often a major problem in the shrimp farming system was IMNV (Infectious Myonecrosis Virus). Bioflok technology was one alternative that can be done to overcome the problem of cultivation waste. Even able to provide more benefits because in addition to reducing inorganic nitrogen waste, can also provide additional feed for fish cultivation so as to improve the growth and efficiency of feed. The addition of probiotics in biofloc was also expected to improve the growth performance of white shrimp. This study was aimed to evaluate the use of bioflock combined with probiotics on the growth performance of vaname shrimp (Litopenaeus vannamei). This research will be conducted for 5 months. The treatment provided is the addition of commercial probiotics in culture medium with biofloc system and fermented pellet feed with various commercial probiotics, ie probiotics I + biofloc (1), probiotics II + biofloc (2), probiotics III + biofloc (3), positive control (biofloc culture medium and without the addition of commercial probiotics) (4), and negative control (without probiotics + without biofloc) (5). The results obtained for growth performance ie on treatment 2 with 80% of survival rate, the value of daily growth rate of 4.9 and the value of feed conversion ratio of 1.41.